Impact of the COVID-19 pandemic and a supertyphoon: A quantitative study in Cebu, Philippines. - Michelle Ylade; Bipin Adhikari; Maria Vinna Crisostomo; Jedas Veronical Daag; Anna Maureen Cuachin; March Helena Lopez; Angela Macasero; Kristal An Agrupis; Jacqueline Deen (PLOS Global Public Health)
Pandemics and natural disasters are recognized to cause major disruptions. The main objective of this study was to explore the impacts of COVID-19 and supertyphoon Odette in Cebu, Philippines. A total of 2630 participants were interviewed exploring the impacts of COVID-19 and supertyphoon Odette. The majority of the respondents (2486/2630; 94.5%) had financial problems due to COVID-19. Almost three out of four respondents (1962/2630; 74.6%) experienced moderate to severe impact on their mental health. Almost a third of the respondents (874/2630; 33.2%) reported moderate to severe impact on their physical well-being, mostly related to weight-related disorders. Almost half of the respondents (1248/2630; 47.5%) experienced moderate to severe impacts on their relationships with family members, relatives, friends and neighbors. More than two-thirds of the respondents (1673/2360; 63.6%) reported moderate to severe financial problems due to supertyphoon Odette. Households who were financially impacted by Supertyphoon Odette were more likely not have recently migrated to their current residence (p<0.001), and to have lower monthly expenditure (p = 0.020). The specific financial problems reported by the majority (1671/2360; 64.5%) were increased expenses, followed by inability to work (623/2360; 23.7%). Almost two-thirds of the respondents (1680/2360; 63.9%) reported having mental health problems. The majority of respondents (1853/2360; 70.5%) had moderate to severe impacts on their living conditions, disrupted by interruption in electricity, water supplies, and house damage. The COVID-19 pandemic and supertyphoon Odette had multi-faceted effects with immediate and long-term implications and greater impacts among poorer households. Public health measures to counteract the consequences of both of these incidents require a multi-pronged and targeted approach.